If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5(2x+3)=3(2x+5)+3x
We move all terms to the left:
5(2x+3)-(3(2x+5)+3x)=0
We multiply parentheses
10x-(3(2x+5)+3x)+15=0
We calculate terms in parentheses: -(3(2x+5)+3x), so:We get rid of parentheses
3(2x+5)+3x
We add all the numbers together, and all the variables
3x+3(2x+5)
We multiply parentheses
3x+6x+15
We add all the numbers together, and all the variables
9x+15
Back to the equation:
-(9x+15)
10x-9x-15+15=0
We add all the numbers together, and all the variables
x=0
| v+4.36=9.71 | | (a-7)/5=13 | | 0.08x+3.2=0.1x+2.8 | | 7x+10=74-x | | 4x+1/4=177/4 | | 5x-5=-25/6 | | 36=y-5y=12 | | -3/7x-1=17/7 | | 8x+3=69 | | 7x+10=23/3 | | 4-4x=14/3 | | 2/3x+2=43/18 | | 1/3x+3=88/27 | | 6x=2-x=12 | | -4/7x+9=103/7 | | 35=29+x | | 6x+9/10=-291/10 | | 14-8x=2(x-28) | | u+22=33 | | 3x2–x–2=0 | | 2-6x=68 | | 4x+14=-7+3x | | 2x^¨2+28x-11152=0 | | -9b-8=-179 | | .1x+x=57.30 | | .1x+x=78.10 | | -54=-9-3x | | .1x+x=78.30 | | 5+11x=115 | | 3*1-5y=37 | | 7-4v=-61 | | x^2-35x-2448=0 |